Laser ablative decoration of micro-diamonds by gold nanoparticles for fabrication of hybrid plasmonic–dielectric antennae. (5th May 2017) - Ivanova, A K; Ionin, A A; Khmelnitskii, R A; Kudryashov, S I; Levchenko, A O; Mel'nik, N N; Rudenko, A A; Saraeva, I N; Umanskaya, S P; Zayarny, D A; Nguyen, L V; Nguyen, T T H; et al.
Abstract: Hybrid plasmonic–dielectric antennae are fabricated by laser ablation of gold in water sols of micro-diamonds. Electron microscopy and energy-dispersive x-ray spectroscopy of their deposits on a silicon wafer surface indicate close proximity of gold nanoparticles and micro-diamonds, which is supported by photoluminescence studies demonstrating strong (eight-fold) damping of micro-diamond luminescence owing to the attachment of the gold nanoparticles. UV–near-IR spectroscopy of their sols reveals a considerable plasmonic effect, related to red spectral shifts of surface plasmon resonance for the gold nanoparticles in the laser-ablation-fabricated antennae.